Edge‐enabled IoT gateway criteria selection and evaluation. (28th February 2019) - Papcun, Peter; Kajati, Erik; Cupkova, Dominika; Mocnej, Jozef; Miskuf, Martin; Zolotova, Iveta
Summary: In this contribution, we define the concept of transferring intelligence from the cloud to the edge of the network and highlight its importance in modern IoT architectures. It leads to edge‐enabled IoT solutions, where intelligence is distributed to the end devices, ie, edge of the network. The IoT gateway is a middle‐ware between devices and cloud and facilitates computations and communication. We have encountered a research gap and decided to propose our solution on creating an edge‐enabled IoT gateway and evaluating its rating by functionality. In the beginning, we describe the general architecture where we demonstrate the location of the edge‐enabled IoT gateway in edge‐enabled solution. Then, we discuss a selection of major criteria, which could be implemented to any edge‐enabled solution. In the end, we evaluate our proposed edge‐enabled IoT gateway and also compare several scientific works focused on IoT gateway design according to our criteria.